2002
DOI: 10.1016/s1388-2457(02)00266-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task difficulty on evoked gamma activity and ERPs in a visual discrimination task

Abstract: Objective: The present study examined oscillatory brain activity of the EEG gamma band and event-related potentials (ERPs) with relation to the difficulty of a visual discrimination task.Methods: Three tasks with identical stimulus material were performed by 9 healthy subjects. The tasks comprised a passive control task, and an easy and a hard visual discrimination task, requiring discrimination of the color of circles. EEG was recorded from 26 electrodes. A wavelet transform based on Morlet wavelets was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 59 publications
12
73
2
2
Order By: Relevance
“…Such preparatory effects have been demonstrated by studies of anticipation and task difficulty. These studies revealed that amplitudes of evoked GBA are larger for anticipated stimuli (Fründ et al, 2008b), for speeded compared to slow manual responses (Fründ et al, 2007b) and for difficult compared to easy discrimination tasks (Senkowski and Herrmann, 2002). Evoked GBA was also found to correlate with speed and accuracy of discrimination of a circular arrangement of Gabors embedded in an otherwise random Gabor array; its latency correlated with reaction times while its amplitude correlated with accuracy (Schadow et al, 2009).…”
Section: Evoked Gba Reflects Interactions Between Stimulus Representamentioning
confidence: 91%
“…Such preparatory effects have been demonstrated by studies of anticipation and task difficulty. These studies revealed that amplitudes of evoked GBA are larger for anticipated stimuli (Fründ et al, 2008b), for speeded compared to slow manual responses (Fründ et al, 2007b) and for difficult compared to easy discrimination tasks (Senkowski and Herrmann, 2002). Evoked GBA was also found to correlate with speed and accuracy of discrimination of a circular arrangement of Gabors embedded in an otherwise random Gabor array; its latency correlated with reaction times while its amplitude correlated with accuracy (Schadow et al, 2009).…”
Section: Evoked Gba Reflects Interactions Between Stimulus Representamentioning
confidence: 91%
“…The first step in these preprocessing procedures also had the effect of removing phase-locked activity from the signals being analyzed. The resulting nonphase-locked activity, which had previously been considered ''noise'' in computations of ERPs, has been increasingly recognized as containing rich task-relevant information [Ding et al, 2000;Kalcher and Pfurtscheller, 1995] and in some cases to reflect task-related cortical activity that cannot be inferred solely from the ERP [Crone et al, 2001a;Senkowski and Herrmann, 2002;Senkowski et al, 2007]. Perhaps more importantly, in a recent comparison of causality analyses with and without subtraction of the ensemble average [Oya et al, 2007], spurious causality responses were observed when the subtraction was not done.…”
Section: Experimental Datamentioning
confidence: 99%
“…Evoked gamma activity has been observed following auditory (Marshall et al, 1996;Yordanova et al, 1997a,b;Karakas and Basar, 1998;Haig et al, 1999Haig et al, , 2000aGurtubay et al, 2001;Kaiser and Lutzenberger, 2001;Muller et al, 2001;Palva et al, 2002;Debener et al, 2003;Karakas et al, 2003), visual (Tallon-Baudry et al, 1996;Herrmann et al, 1999;Herrmann and Mecklinger, 2000b;Braeutigam et al, 2001;Bottger et al, 2002;Senkowski and Herrmann, 2002;Watanabe et al, 2002) or somatosensory stimuli (Desmedt and Tomberg, 1994;Salenius et al, 1996). It has been observed at early (0 -150 ms) and later (200 -300 ms) (Herrmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%